DESAIN KURSI SANTAI MULTIFUNGSI ERGONOMIS DENGAN MENGGUNAKAN PENDEKATAN ANTROPOMETRI - Tina Hernawati Suryatman; Roni Ramdani (Journal Industrial Manufacturing, 2019)
The existing lounge chairs have a function just as a place for people to relax without any other functions. With the design of multifunctional lounge chair products, we will find it easier to do other things without having to have a lot of things and move to another place to just take something. The phenomenon that occurs at this time is still not a lot of ergonomic multifunctional leisure chair designs because it puts more design and additional functions without considering the comfort of its users. For this reason, research was conducted to design a more ergonomic multifunctional lounge chair. Anthropometric used to design ergonomic multifunctional lounge chairs based on anthropometric approaches are popliteal height (tpo), popliteal length (ppo), shoulder width (lb), hip width (lp), sitting elbow height (tsd), and shoulder height sit (tbd). This ergonomic multifunctional lounge chair is designed to make it easier for users to use chairs with many functions, an important component in this multifunctional lounge chair through a second adjustable chair that functions so that it can be used for 2 people, then 2 mini tables that serve to put the book read, and a drawer that serves to store items that are often used to accompany leisure.Key words :  Anthtopometry, Product Design, Ergonomics, Design, Lounge Chairs